The effects of a solar eclipse on animals behavior - Özbey, O; Aysöndü, MH; Özer, H; Simsek, ÜG (Scientific Technical Research Council Turkey, 2004)
This study was conducted to determine the effects of the solar eclipse of August 11, 1999, on the behavior of birds (chickens, Pekin ducks, gulls, crows and sparrows), cattle, bees and horses. The animals were observed for 6, from 11 am to 5 pm. Abnormal and extreme behaviors were determined at the observation times. Birds, cattle, bees and horses felt the solar eclipse about 45, 20. 65 and 35 minutes before it occurred, respectively. They showed this via their behaviors. When the total solar eclipse occurred between 2:37 and 2:39 pm, laying hens and broilers crowded together. They were very quiet and restless. Gulls stopped flying and were quiet and restless. Sparrows and crows were careful and afraid and they did not fly or sing. They crowded together in the trees and they were very nervous and afraid. All horses and cattle become very quiet, they did not move and they sniffed the air. They were very restless, shaking their tails and heads. A slight buzzing sound come from the bee hives. In conclusion, birds, cattle, bees and horses exhibited abnormal and extreme behaviors during the solar eclipse.
Tam güneş tutulmasinin hayvanlarin davranişlari üzerine etkisi
Keywords: Solar Eclipse; birds; cattle; honeybees; horses; animal behavior